ROLE OF GREEN MARKETING IN PROMOTING ECO-CONSTRUCTION IN ALGERIA - Nadia, Boumediene; Amel, Dinar (The journal of contemporary issues in business and government, 2023)
Confronting sustainable development means that companies must take into account the following issues: global warming, greenhouse gases, ozone layer, drinking water, forest, land and sea conservation, waste management, recycling, reuse, recovery, "green" products and services... etc; as well as educating people through a good green communication strategy that is one of the components of the green marketing to react in the same way to have a clean and healthy environment. As a result of technological advances and population growth, human beings are the main cause of so-called "climate change". Therefore, ecological construction must be established within each society. Having an ecological home corresponds to the concern to build a more environmentally friendly housing.